The Territorial Agenda 2030: Towards a common language? A review of a conceptual framework - Henriques, C. (2021)
The Territorial Agenda 2030 aims to provide multi-level strategic orientation to increase cohesion and overcome the 21st century pressing challenges. In multilingual contexts, the ideas and concepts communicated in such agendas must be clear and well-defined. In our study, we conducted a content analysis of the concepts of environment, inequality, justice, sustainability, territory and transition in contrast with former versions of this agenda. We found that, since 1983, the Territorial Agenda conceptual framework changed significantly in its meaning and semantic universe of reference.